Maturidade em governança corporativa: uma pesquisa aplicada às entidades EIRELI - Holanda, Madson André Pereira de (2014)
The adoption of good corporate governance practices benefit entities, the Code of best practices in corporate governance gather recommendations, principles, on the subject, but do not provide a systemic and teleological script aiming to entities that adopt or verify adherence to what is suggested. This paper focuses diagnose, analyze and compare the level of maturity in corporate governance of 17 entities named EIRELI - Companies Limited Liability single, medium-sized entities duly registered in JUCEPE - Board of Trade of Pernambuco, in the object activity CNAE 2.0. in the segment of services and rental of cranes, winches, containner, opting for tributary of the taxable income system and headquartered in the state of Pernambuco in that refers to the adoption of the principles of corporate governance. Search this is done through the use of questionnaires consisting of eighty closed and binary issues, aiming to diagnose, analyze and compare the level of maturity in corporate governance, sidewalks issues in the Code of Best Corporate Governance Practices disseminated by IBGC (2009). Being the questionnaires divided into four corresponding principles: (i) the principle of transparency; (ii) Equity Principle; (iii) Principle of Corporate Responsibility, and (iv) Principle of Accountability. Each principle is divided into levels, as follows: Level 1 - Started; Level 2 - Expanded; Level 3 - Institutionalized; Level 4 - Enhanced and Level, 5 - Complete. Therefore, the eighty issues will be divided into four groups represented by the principles of GC, further subdivided into five levels, each level corresponding to the four binary questions. The research methodology preliminarily adopted the study Bramont (2012), but the guidelines in what concerns the composition of the questionnaires were adapted to the reality of EIRELI, a fact that gives originality to study in screen. This research is classified as exploratory and descriptive, based on secondary data sources, data analysis in the public domain and interviews with the presidents of companies in EIRELI mode. The research aims to demonstrate the relevance of new EIRELI entity, established in 2011 through the 12,441 number of Law, for the Brazilian business scenario